Falcarindiol Enhances Cisplatin Chemosensitivity of Hepatocellular Carcinoma via Down-Regulating the STAT3-Modulated PTTG1 Pathway - Hong, Han; Jin, Zhengkang; Qian, Tao; Xu, Xiaoyong; Zhu, Xiang; Fei, Qiang; Yang, Jiamei; Sui, Chengjun; Xu, Minhui (Frontiers in Pharmacology, 2021)
Hepatocellular carcinoma (HCC) is the most frequent primary liver malignancy globally and the third leading cause of cancer-related death. Chemotherapy is one of the main methods in treating HCC, while recent studies have found that the resistance of HCC to chemotherapeutic drugs reduces the efficacy of the chemotherapy. Falcarindiol (FAD) is a cytotoxic and anti-inflammatory polyacetylenic oxylipin found in food plants of the carrot family (Apiaceae), while its role in HCC remains to be explored. Here, HCC cells (Huh7 and LM3) were treated with FAD at different doses. Cell proliferation was tested by the cell counting kit-8 (CCK-8) method and colony formation assay, while the apoptosis was monitored by flow cytometry. The profiles of apoptosis-related proteins (Bax, bcl2, and Caspase-3), DNA repair proteins (Rad51, BRCA1 and MDC1) and signal transducer and activator of transcription 3 (STAT3)/ Pituitary Tumour Transforming Gene 1 (PTTG1) were verified by western blot (WB) or quantitative reverse transcription-polymerase chain reaction (qRT-PCR). The interaction between STAT3 and PTTG1 was verified by immunoprecipitation (IP). In addition, a xenograft tumor model was constructed in mice to explore the anti-tumor effects of FAD in vivo, and immunohistochemistry (IHC) was performed to count the number of Ki67-stained cells. As a result, FAD inhibited HCC cells’ proliferation, DNA repair, and facilitated their apoptosis, and also enhanced cisplatin (DDP) chemosensitivity. The Combination index (CI) evaluation showed that FAD and DDP had synergistic effects in repressing HCC cells proliferation. Besides, FAD dampened the STAT3/PTTG1 pathway expression. Further studies revealed that inhibiting STAT3 enhanced the inhibitive effect of FAD on HCC cells, whereas overexpressing PTTG1 attenuated the anti-tumor effect of FAD. Overall, our study illustrated that FAD is a potential anticancer drug and strengthens the chemosensitivity of HCC cells to DDP by inhibiting the STAT3/PTTG1 pathway.